Co-transport of graphene oxide and heavy metal ions in surface-modified porous media. (March 2019) - Yin, Xianqiang; Jiang, Yanji; Tan, Yuehui; Meng, Xiangmin; Sun, Huimin; Wang, Nong
Abstract: The ability to predict the transport of heavy metal ions in porous media with different surface characteristics is crucial to protect groundwater quality and public health. In this study, the effects of graphene oxide (GO) on co-transport and remobilization of Pb 2+ and Cd 2+ in humic acid (HA), smectite, kaolinite, and ferrihydrite-coated sand media were evaluated via laboratory packed-column experiments. Scanning electron microscope and energy dispersive X-ray analysis showed that the surface morphology of the coated sands was quite different and that ∼56.7–89.9% of the surface was covered by the coating and the major elemental components were C, O, Si, Al, and Fe. GO exhibited high mobility in HA, kaolinite, and smectite-coated sand, but showed high retention in ferrihydrite-coated sand. While GO reduced the transport of Pb 2+ and Cd 2+, both metal ions also reduced the mobility of GO in coated-sand columns. Elution experiments revealed that GO led to the remobilization and release of the previously sorbed Pb 2+ and Cd 2+ from the coated sand. However, GO could not release Pb 2+ and Cd 2+ from smectite-coated sand columns, probably because smectite has stronger adsorption affinity to the heavy metals than GO. Derjaguin-Landau-Verwey-Overbeek calculations were employed and explained the GO transport behavior in the columns well. Furthermore, the advection-dispersion-reaction equation simulated the cotransport of Pb 2+ and Cd 2+ with GO in the coated sand well. These results are expected to provide insight into the potential impact of coexisting nanomaterials with contaminants in vulnerable soil and groundwater systems. Graphical abstract: Image 1 Highlights: HA, smectite, kaolinite, and ferrihydrite were used to coating quartz sand. The mobility in the coated sand column is GO > Cd 2+ > Pb 2+ . Co-transport mobility of GO and Pb 2+ or Cd 2+ in coated sand column was decreased. GO released Pb 2+ or Cd 2+ from coated sand and smectite is the smallest. The DLVO theory could well explain the transport behavior.